Intrinsic Domain and Loop Dynamics Commensurate with Catalytic Turnover in an Induced-Fit Enzyme - Davulcu, Omar (2009)
Arginine kinase catalyzes reversible phosphoryl transfer between ATP and arginine, buffering cellular ATP concentrations. Structures of substrate-free and -bound enzyme have highlighted a range of conformational changes thought to occur during the catalytic cycle. Here, NMR is used to characterize the intrinsic backbone dynamics over multiple timescales. Relaxation dispersion indicates rigid-body motion of the N-terminal domain and flexible dynamics in the I182-G209 loop, both at milli-second rates commensurate with k(cat), implying that either might be rate limiting upon catalysis. Lipari-Szabo analysis indicates backbone flexibility on the nanosecond timescale in the V308-V322 loop, while the rest of the enzyme is more rigid in this timescale. Thus, intrinsic dynamics are most prominent in regions that have been independently implicated in conformational changes. Substrate-free enzyme may sample an ensemble of different conformations, of which a subset are selected upon substrate binding, with critical active site residues appropriately configured for binding and catalysis.